2006
DOI: 10.1097/01.icl.0000189038.74139.4a
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopy Findings in Keratoconus

Abstract: : Quantitative and qualitative structural changes were observed in all corneal layers in eyes with keratoconus by using slit-scanning confocal microscopy. The changes at all levels were more prominent in eyes with severe keratoconus. This noninvasive in vivo technique may prove to be useful in the diagnosis and follow-up of keratoconus and in the understanding of its pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
100
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 15 publications
8
100
6
Order By: Relevance
“…This finding was supported by Ucakhan et al, who reported the presence of Vogt's striae in the anterior stroma of keratoconic eyes with moderate and severe (3)(4)(5)(6)22). In the present study, polymegathism and pleomorphism were higher in patients with keratoconus than in those with healthy eyes.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This finding was supported by Ucakhan et al, who reported the presence of Vogt's striae in the anterior stroma of keratoconic eyes with moderate and severe (3)(4)(5)(6)22). In the present study, polymegathism and pleomorphism were higher in patients with keratoconus than in those with healthy eyes.…”
Section: Discussionsupporting
confidence: 81%
“…Interloss in keratoconus could be associated with disease severity (3). Ucakhan et al reported that morphological alterations, such as folds in the anterior stroma, elongation of keratocyte nuclei, increased polymegathism and pleomorphism and decreased keratocyte density in stroma, were more evident in the severe stages of keratoconus than in the early stage (4). By contrast, Weed et al found that the anterior and posterior stromal keratocyte densities increased in moderate and advance keratoconus compared with the controls (5).…”
Section: Examinersmentioning
confidence: 80%
See 3 more Smart Citations